Impact of Leadership in Scaling Startups in EdTech Product Space in Emerging Markets Such as India - Chatterjee, Ramya (Global journal of Business and Integral Security, 2024)
This research investigates the impact of leadership on scaling startups in the EdTech product space in emerging markets such as India. The main aim of this study is to examine the significant impact of leadership in the expansion of start-ups in the Ed-Tech sector within emerging markets like India. The further objectives of the study are: 1. To identify the role of leadership in business growth and performance in context to Indian Ed-tech startups 2. To determine the main components of leadership effectiveness that contributes to the scalability of start-ups and specifically Indian Ed-tech startups 3. To analyze the impact of strong leadership on the scaling of start-ups and specifically Indian Ed-tech startups. The results of the study indicate that leadership plays a critical role in scaling EdTech startups in emerging markets. The research also explored how different leadership styles and behaviors affect the growth and success of EdTech startups in emerging markets. The study employs mixed-methods of research by combining both quantitative and qualitative analysis, to create a more holistic and nuanced understanding of the research topic, providing a more robust and reliable conclusion. Inputs taken from EdTech entrepreneurs & employees, investors, and industry experts. The data analysis part of the research was carried out using descriptive statistics, reliability analysis, factor analysis and regression analysis. Descriptive statistics was used to represent the changes that occurred in the collected data. Through calculating the frequencies and graphing them, trends and patterns within the data are clearly highlighted in a precise manner. Reliability analysis was used as there was Likert scale type data. The Cronbach alpha tests the internal consistency of the data and gives an indication on whether or not the data is reliable to carry out tests and make conclusions. Factor analysis is a dimension reduction method used to identify the important factors from the factors considered. And finally, regression analysis was used to identify relationships between variables and test the hypotheses. By implementing regression analysis to test the hypotheses, the analysis resulted in the following conclusions that Adaptability, Strong communication, Interpersonal skills, Creativity, Decision Making, Self-Discipline, Resilience and Empowerment as a leadership attribute in scaling start-ups do have significant impacts on Ed-tech businesses scaling performance. The research also reveals that certain contextual factors in emerging markets, such as limited access to capital and talent, pose unique challenges to scaling EdTech startups. However, effective leadership can help overcome these challenges and enable sustainable growth in the EdTech sector. The findings of this study have practical implications for EdTech entrepreneurs, investors, and policymakers, and can inform the development of effective leadership strategies to promote the growth and success of EdTech startups in emerging markets.